First-Aid System for Marathon Athletes Based on Telemedicine Technology - Caixia Chen; Shuai Liu (Applied Bionics and Biomechanics, 2022)
With the emphasis on sports in the region and the improvement of people’s living standards, more and more people participate in various sports and activities including marathon, so that more and more cities are hosting or even vying for it. With the marathon, not only the joy of successfully holding the event, but also the pain of the contestants and even the sadness of sudden death. In order to reduce the occurrence of such problems, this paper studies the emergency system of marathon runners based on telemedicine technology. The experimental results show that the research on first-aid bears for athletes based on telemedicine technology can save a lot of time and managers, improve the efficiency of first aid by 3.45%, and provide first-aid services for injured athletes at the first time, so as to ensure the health of athletes, ensuring the confidence and well-being of athletes participating in the marathon.